Bento Box User Experience Study at Franklin University - Jaffy, Marc (Information Technology and Libraries, 2020)
This article discusses the benefits of the bento-box method of searching library resources, including a comparison of the method with a tabbed search interface. It then describes a usability study conducted by the Franklin University Library in which 27 students searched for an article, an ebook, and a journal on two websites: one using a bento box and one using the EBSCO Discovery Service (EDS). Screen recordings of the searches were reviewed to see what actions users took while looking for information on each site, as well as how long the searches took. Students also filled out questionnaires to indicate what they thought of each type of search. Overall students found more items on the bento-box site, and indicated a slight preference for the bento-box search over EDS. The bento-box site also provided quicker results than the EDS site. As a result, the Franklin University library decided to implement bento-box searching on its website.